Safety culture awareness and practices in the malaysian mining industry : A preliminary study - Siti Natrah, Ismail; Azizan, Ramli (2022)
Presently, safety culture is receiving attention for the prevention of mining disaster or accidents. The mining industry in Malaysia has been around for 200 years and fortunately, to date, there is no large-scale mining disaster that has occurred in Malaysia. However, that led to a lack of study on the safety culture in Malaysian mining industry. The study aims at exploring the current status of safety culture awareness and practices in Malaysian mining industry. A qualitative, open-ended interview session was conducted in April 2021 via the online Google Meet platform. Six mining experts had agreed and volunteered to be involved in the interview session. Three themes were created: (1) Significance of safety culture in mining; (2) Factors that make up the safety culture in mining industry; and (3) Adopting safety culture in mining industry. Three themes and eight sub- themes were validated by the mining expert interviewers. In conclusion, the current status of safety culture awareness and practices in mining industry is very low. It was observed that there was a huge gap between small-scale and large-scale mining operation in Malaysia. For small-scale mining operation, it was below 50%, where one of expert claimed it to be approximately 30%. It is recommended that the top management of mining companies have their mindset changed, not only focusing on the profit but to strengthen the safety aspects as well. A good safety culture will increase the workers and operational productivities and prevent mining accident or disaster in Malaysia in the near future.